Capacities of the Nutrition Sector in Senegal - Deussom N., Gabriel; Wise, Victoria; Ndione, Marie Solange; Gadiaga, Aida (World Bank, Washington, DC, 2019)
In Senegal, government commitment to nutrition has increased progressively in recent decades. Thecreation in 2001 of the Cellule de Lutte Contre la Malnutrition (the Nutrition Coordination Unit) (CLM) and its Bureau Exécutif National (the National Executive Bureau) (BEN) marked a major turning point, as did an increase in annual budget allocations to nutrition (from US$0.3 million in 2002 to US$5.7 million in 2015) and concomitant intensification of community-based nutrition interventions. This commitment is reflected in the improvement of nutrition indicators. With a 46 percent reduction in under-five stunting, from 34.4 percent in 1992 to 19.4 percent in 2014, Senegal has witnessed one of the biggest rates of improvement in the fight against undernutrition in the world and currently has one of the lowest rates of stunting in Sub-Saharan Africa (Spray 2018). However, these developments have not led to greater visibility of pronutrition interventions in relevant sectors such as agriculture, livestock, health, education, social protection, and hydraulics. Moreover, some nutrition-specific problems with major consequences—low birthweight, iron-deficiency anemia, adolescent nutrition, and maternal undernutrition—still receive little attention. These shortcomings threaten the gains achieved in recent decades. Recognizing the challenge, the government of Senegal joined the SUN Movement in 2011 and adopted the United Nations REACH approach in 2014. Both initiatives aim to strengthen institutional capacity and facilitate a multisectoral process to help governmentsplan, prioritize and more efficiently manage nutrition actions involving multiple stakeholders. With respect to national policy, the Document de Politique National de Développement de la Nutrition (National Policy for the Development of Nutrition) (PNDN) has been adopted for the period 2015 to 2025. The PNDN will be operationalized through a multisectoral nutrition strategy, the Plan Stratégique Multisectoriel de la Nutrition (Multisectoral Nutrition Strategic Plan) (PSMN). The PSMN is designed as a sectoral reform program to broaden coverage and improve the quality of nutrition services.Against this background, this institutional and organizational capacity assessment (IOCA) analyzes the performance of Senegal’s nutrition sector and makes 8 Analysis & Perspective: 15 Years of Experience in the Development of Nutrition Policy in Senegal recommendations for strengthening implementation of the PNDN and forthcoming PSMN.